The crosslinking of poly (ether ether ketone): Thermally and by irradiation. Issue 22 (9th February 2015) - Al Lafi, Abdul G.; Parker, David J.; Hay, James N.
ABSTRACT Crosslinking of amorphous poly (ether ether ketone) films was carried out by means of thermal annealing at 400°C as well as by irradiation with 11.0 MeV proton beam at different dose rate ranging from 1.75 to 15.5 kW g−1. The materials properties of the resulting films were investigated by mean of light microscopy, sol‐gel analysis, two‐dimensional infra‐red correlation spectroscopy, 2DCOS‐IR, and differential scanning calorimetry (DSC). It was found that both chain scission and crosslinking yields were decreased by an increase of dose rate and the ratio of crosslinks to chain scission was increased from 0.9 to 1.4. The 2DCOS‐IR analysis in the region 1400–1800 cm−1 showed progressive development of new bands at 1470 and 1740 cm−1, which have been used to support the presence of crosslinking and chain scission reactions. The glass transition temperature also increased in line with increasing crosslinking density, but the results showed a limiting plateau value for the glass transition <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj9kz2612" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Tg</alternatives>, which depended only on the absorbed dose. This suggests that crosslinking was limited and did not increase after a specific value of the dose rate. Crosslinking by irradiation has many advantages over thermal annealing; in particular it is a one step rapid process producing a variety of homogeneously crosslinked, good quality films available for chemical modification. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41999.